Analisis Proses Manajemen Risiko Teknologi Informasi Sistem Infrastruktur Telekomunikasi (InfraTel) PT. Telkom Indonesia menggunakan Framework ISO 31000:2009 - Nazruddin Safaat H (UIN Sultan Syarif Kasim Riau, 2012)
Telecommunications Infrastructure is a very important for PT. Telkom Indonesia, because asTelecommunications company, Telkom’s services and products can not be separated from the use of theTelecommunications Infrastructure. Besides it is important for the company, Telkom’sTelecommunicationsInfrastructure often impaired the events that occurred in Indonesiasuch as natural disasters (floods,lightning, hurricanes, earthquakes, tsunamis), the incidence of fires and other events. ThereforeTelkom'sTelecommunication Infrastructure risk management is very important to achievement of the goals of thecompany.This research examines IT risk management based on ISO 31000 with a case study Telkom'sTelecommunications Infrastructure.The research methodology used